Mapping the Evolution and Future Directions of ISO/IEC 25010: A Bibliometric and Thematic Analysis - Rojas, Hesmeralda; Renteria, Ronald; Duran, Virgilio Martinez; Gutiérrez, Yuliana Tomaylla; Cabrera, Manuel J. Ibarra; Aminuddin, Afrig (Engineering, Technology & Applied Science Research, 2025)
This study is a bibliometric analysis of 1,613 scientific articles focused on the ISO/IEC 25010, an international standard for software quality evaluation. The data were taken from the Scopus repository, from 1990 to 2025, indicating a consistent rise in the research productivity, reaching its zenith in 2023, providing further evidence of the international significance of ISO/IEC 25010 in areas, such as public administration, finance, education, and healthcare. While subjects of computer science and engineering continue to thrive, interdisciplinary applications are gaining popularity. The thematic mapping, keyword co-occurrence analysis, and publication trends revealed various articles centered around the normative models, user experience, empirical validation, structural design, quality assessment, and predictive modeling. These areas of expertise are founded on concepts, such as the software quality, quality control, and ISO standards, in addition to usability, machine learning, and cloud computing. International collaboration networks show strong connections between Spain, Philippines, and Indonesia. However, despite its flexibility, the standard faces challenges, including structural rigidity and a lack of installation, especially for Small and Medium-sized Enterprises (SMEs). The present study emphasizes the necessity for hybrid approaches that integrate ISO/IEC 25010 with agile and AI-driven methodologies.